If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3n + 3) = 6(7n + 3) + 5 Reorder the terms: 6(3 + 3n) = 6(7n + 3) + 5 (3 * 6 + 3n * 6) = 6(7n + 3) + 5 (18 + 18n) = 6(7n + 3) + 5 Reorder the terms: 18 + 18n = 6(3 + 7n) + 5 18 + 18n = (3 * 6 + 7n * 6) + 5 18 + 18n = (18 + 42n) + 5 Reorder the terms: 18 + 18n = 18 + 5 + 42n Combine like terms: 18 + 5 = 23 18 + 18n = 23 + 42n Solving 18 + 18n = 23 + 42n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-42n' to each side of the equation. 18 + 18n + -42n = 23 + 42n + -42n Combine like terms: 18n + -42n = -24n 18 + -24n = 23 + 42n + -42n Combine like terms: 42n + -42n = 0 18 + -24n = 23 + 0 18 + -24n = 23 Add '-18' to each side of the equation. 18 + -18 + -24n = 23 + -18 Combine like terms: 18 + -18 = 0 0 + -24n = 23 + -18 -24n = 23 + -18 Combine like terms: 23 + -18 = 5 -24n = 5 Divide each side by '-24'. n = -0.2083333333 Simplifying n = -0.2083333333
| x^3-8x^2-5x+40=0 | | 15=2m-3 | | 12+x/11=9 | | x(x)+15x=-56 | | 2.2x-2.4=13 | | 3b^2-7b=40 | | m^4+13m^3+22m^2=0 | | x(x)+10x+25=0 | | 3(x-2)+10x=33 | | 12+m/6=15 | | 8y-16+5y=-59 | | s(s)+10s+24=0 | | 7=4x-5 | | 50-2h=44 | | 4x-8=28-x | | -15x=23(4+4)/(-23) | | 4(-7+x)=5x-1/4 | | -15x=23(4+4)/23 | | c/5+8=-5 | | 8/3+2.4 | | 18+9m=288 | | 15x=23(4+4)/23 | | 9x+4=1+2x | | x+7/4=8/5 | | 2.8x-3.3=-8.9 | | 2(9x+7)-8x=2(5x+4)-12 | | -3c-2+7=4c+2-6c | | -8-6x=28 | | 6y+3=5y-9 | | 2(x-1)=4x+1 | | -12+20p=588 | | 4/3x=52 |